The rise and fall of Manuel Merino: analysis of journalistic discourses (9/11/2020 - 15/11/2020) - Anticona Alegre, Angie Jennifer (2021)
In November 2020, the Congress of the Republic of Peru decided to vacate Martín Vizcarra. As a result, Manuel Merino de Lama, president of Congress at the time, came to power. Faced with this event, many citizens, from different parts of the national territory, expressed their discontent and went out to protest and march. This situation affected the politics of the country. The Peruvian and foreign media reported the events minute by minute and in real time. On the web platforms of the newspapers, it was possible to observe how the news media had a different perception of reality. Therefore, this research aims to analyze and compare the meaning of media coverage during the marches against the presidency of Manuel Merino, on the website of the newspapers El Comercio and La República, between 9/11/20 to 15/11/20. The research level is descriptive-comparative and the design is non-experimental. The technique used is content analysis and the instrument is the analysis matrix. The population is 295 informative web notes of the newspaper El Comercio and 274 of the newspaper La República. The sample has three notes from each diary.